2002
DOI: 10.1038/ng956
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide retroviral insertional tagging of genes involved in cancer in Cdkn2a-deficient mice

Abstract: We have used large-scale insertional mutagenesis to identify functional landmarks relevant to cancer in the recently completed mouse genome sequence. We infected Cdkn2a(-/-) mice with Moloney murine leukemia virus (MoMuLV) to screen for loci that can participate in tumorigenesis in collaboration with loss of the Cdkn2a-encoded tumor suppressors p16INK4a and p19ARF. Insertional mutagenesis by the latent retrovirus was synergistic with loss of Cdkn2a expression, as indicated by a marked acceleration in the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(157 citation statements)
references
References 26 publications
4
148
2
1
Order By: Relevance
“…Finally, as uPAR overexpression may participate in tumorigenesis in the absence of the Ink4a gene products (Lund et al, 2002) we analysed p19 À/À MEFs, lacking one gene product of this locus, and found that uPAR overexpression failed to decrease growth (Figure 1e), even though it did not stimulate it like Ras V12 . Thus, uPAR can affect cell proliferation only in a p19-positive background.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, as uPAR overexpression may participate in tumorigenesis in the absence of the Ink4a gene products (Lund et al, 2002) we analysed p19 À/À MEFs, lacking one gene product of this locus, and found that uPAR overexpression failed to decrease growth (Figure 1e), even though it did not stimulate it like Ras V12 . Thus, uPAR can affect cell proliferation only in a p19-positive background.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the effect of uPAR on cell proliferation may change depending on which proto-oncogenes and/or tumor suppressor genes are mutated in the cell. Indeed, uPAR is detected as a potential cooperating oncogene in Ink4a Ko mice (Lund et al, 2002). Ink4a Ko mice do not express p16 or p19ARF and are deficient in cell growth control (Serrano et al, 1996).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, mice with a knock out of nfkb2 sequences encoding the C-terminal sequences of p100 have increased numbers of T lymphocytes, enlarged lymph nodes and gastric hyperplasia (Ishikawa et al, 1997). Fourth, in two large-scale retroviral integration screens for mouse lymphoma genes, retroviral integrations in 3 0 coding regions of nfkb2 (and nfkb1) were detected (Lund et al, 2002;Suzuki et al, 2002b).…”
Section: Multiple Familial Trichoepitheliomamentioning
confidence: 99%
“…In addition, Sox4 appears to have a dominant role in conferring oncogenic and metastatic transformation (Rhodes et al, 2004). High levels of Sox4 mRNA expression have been observed in a large number of human tumors including breast, lung, brain, prostate and ovarian cancer, and the Sox4 gene locus has been repeatedly found to be targeted by tumor-promoting retroviral integration in mice (Lund et al, 2002;Suzuki et al, 2002;Shin et al, 2004). Together, these studies support the inclusion of Sox4 as one of the 64 genes that constitute a general cancer signature (Rhodes et al, 2004).…”
Section: Introductionmentioning
confidence: 99%